Activation of autophagy through calcium‐dependent AMPK/mTOR and PKCθ pathway causes activation of rat hepatic stellate cells under hypoxic stress. Issue 5 (1st March 2016) - Jin, Yuepeng; Bai, Yongyu; Ni, Haizhen; Qiang, Li; Ye, Lechi; Shan, Yunfeng; Zhou, Mengtao
Abstract : The activation of hepatic stellate cells (HSCs) is a prominent event in liver fibrogenesis. However, how HSCs are activated in the hypoxic microenvironment remains unclear. Here, we found that hypoxia increased autophagy in rat HSCs. Moreover, hypoxia induced an elevation of the intracellular calcium concentration ([Ca 2+ ]i ), which was abolished by the cytosolic Ca 2+ chelator or the phospholipase C (PLC)‐specific inhibitor. Furthermore, hypoxia‐induced autophagy involved the calcium‐dependent activation of the 5ʹ‐adenosine monophosphate‐activated protein kinase (AMPK)–mammalian target of rapamycin (mTOR) and protein kinase C‐theta (PKCθ) pathways. In addition, hypoxia‐mediated activation of HSCs depended on autophagy. Our results suggest that autophagy induction via the calcium‐dependent AMPK–mTOR and PKCθ pathways might lead to the activation of HSCs during hypoxic stress. Abstract :